Effects of Environmental Sounds on the Guessability of Animated Graphic Symbols. (December 2014) - Harmon, Ashley C.; Schlosser, Ralf W.; Gygi, Brian; Shane, Howard C.; Kong, Ying-Yee; Book, Lorraine; Macduff, Kelly; Hearn, Emilia
Abstract: Graphic symbols are a necessity for pre-literate children who use aided augmentative and alternative communication (AAC) systems (including non-electronic communication boards and speech generating devices), as well as for mobile technologies using AAC applications. Recently, developers of the Autism Language Program (ALP) Animated Graphics Set have added environmental sounds to animated symbols representing verbs in an attempt to enhance their iconicity. The purpose of this study was to examine the effects of environmental sounds (added to animated graphic symbols representing verbs) in terms of naming. Participants included 46 children with typical development between the ages of 3;0 to 3;11 (years;months). The participants were randomly allocated to a condition of symbols with environmental sounds or a condition without environmental sounds. Results indicated that environmental sounds significantly enhanced the naming accuracy of animated symbols for verbs. Implications in terms of symbol selection, symbol refinement, and future symbol development will be discussed.